Ecosystem resilience in action: Evaluating structural, functional recovery, and socio-economic impact of mangroves after restoration efforts - Pañares, Gesila Grace P.; Nicanor, Rio A. (Journal of Degraded and Mining Lands Management, 2026)
Mangrove ecosystems are important biodiversity supporters, coastline protectors and climate stabilizers. However, human activities and environmental changes pose increasing risks to these areas. This study examined the environmental and social impacts of a five-year effort to restore mangroves in Abucayan Sur, Calape, Bohol, Philippines, an area that was once used for fishponds. The project ran from 2019 to 2024. Quadrat sampling was conducted along with transects and local residents were interviewed to assess changes in mangrove species richness, tree growth (basal area, canopy diameter, tree height), the number of macroinvertebrates, and community perceptions of the restoration efforts. The results indicate that both the number of mangroves and their diversity index have improved significantly. After restoration, we identified seven (7) true mangrove species, with Rhizophora apiculata becoming the most common. Structural indicators showed considerable improvement. Both canopy diameter and tree height increased, demonstrating robust forest growth. The number of macroinvertebrates, particularly razor shells and mangrove crabs, increased as habitats recovered, although we observed some short-term declines following typhoons. Socio-economic statistics reveal that coastal communities continue to rely primarily on fishing and other coastal resources for their livelihoods. Despite this, there are still challenges, such as the effects of climate change and a lack of educational opportunities. In conclusion, community-based mangrove recovery can cause considerable ecological restoration and social and economic benefits within five years. The results emphasize the need for continuous monitoring, adjusting management measures, and involving stakeholders for sustainably maintaining and resilient mangrove forests in the Philippines in the long term.